First square both sides to get:
c + 22 = (c + 2)^2
or
c + 22 = c^2 + 4c + 4
Move the terms on the left side to the right side:
c^2 + 3c - 18 = 0
Factor to get:
(c + 6) * (c - 3) = 0.
The solutions are c = -6 and c = 3.
Check to see if these answers work by plugging them into the original equation:
c = -6:
sqrt (-6 + 22) ?= -6 + 2
But, -6 + 2 is a negative number, and you can't get a negative from a square root. So, -6 is extraneous.
c = 3:
sqrt (3 + 22) ?= 3 + 2
5 = 5. So, 3 works.
The answer is: B
Answer:
To find the mean: Multiply midpoints by frequencies, add the subtotals and divide by the total of the frequencies.
Step-by-step explanation:
Put the results in numerical order (in a frequency table this will already be done)
Count the total amount of results and add one.
Divide this by 2 to find the the position of the middle result.
Find the middle result in the numerically ordered list or frequency table.
to solve this we need to isolate the x variable.
subtract 1 from each side: [3x+4] = 6
now we can drop the parentheses and subtract 4 from each side: 3x = 2
divide each side by 3: x = 2/3
Just divide 80 by 7 and see if you don’t get a whole number !
Find the pattern first which is multiply by 5. This problem is geometric sequence so you have to use this formula to find the 10th term:
An=AR^n-1
A(10)=0.1(5)^(10-1)
A(10)=195312.5